BP Gulf Science Data Reveals Ineffectual Subsea Dispersant Injection for the Macondo Blowout - Paris, Claire B.; Berenshtein, Igal; Trillo, Marcia L.; Faillettaz, Robin; Olascoaga, Maria J.; Aman, Zachary M.; Schlüter, Micheal; Joye, Samantha B. (Frontiers in Marine Science, 2018)
After the Deepwater Horizon oil platform explosion, an estimated 172.2 million gallons of gas-saturated oil was discharged uncontrollably into the Gulf of Mexico, causing the largest deep-sea blowout in history. In an attempt to keep the oil submerged, massive quantities of the chemical dispersant Corexit® 9500 were deployed 1522m deep at the gushing riser pipe of the Macondo prospect’s wellhead. Understanding the effectiveness of this unprecedented Sub-Sea Dispersant Injection (SSDI) is critical because deep-water drilling is increasing worldwide. Here we use the comprehensive BP Gulf Science Data (GSD) to quantify petroleum dynamics throughout the 87-day long blowout. The spatio-temporal distribution of petroleum hydrocarbons revealed consistent higher concentrations at the sea surface and in a deep intrusion below 1000 m. The relative importance of these two layers depended on the hydrocarbon mass fractions as expected from their partitioning along temperature and pressure changes. Further, analyses of water column Polycyclic Aromatic Hydrocarbons (PAH) of GSD extensively sampled within a 10-km radius of the blowout source demonstrated that substantial amounts of oil continued to surface near the response site, with no significant effect of SSDI volume on PAH vertical distribution and concentration. The turbulent energy associated with the spewing of gas-saturated oil at the deep-sea blowout may have minimized the effectiveness of the SSDI response approach. Given the potential for toxic chemical dispersants to cause environmental damage by increasing oil bioavailability and toxicity while suppressing its biodegradation, unrestricted SSDI application in response to deep-sea blowout is highly questionable. More efforts are required to inform response plans in future oil spills.